Teachers - Mustofa, M. Ibnu; Riswanto, Riswanto; Putra, Pebri Prandika (Universitas Islam Negeri Palangka Raya, Indonesia, 2023)
Teaching is an activity involving semiotic resources beyond verbal language. Therefore, more studies investigating what semiotic resources are employed and how they are utilized within EFL classroom settings are needed. This study sought to explore the types of semiotic resources employed by two EFL teachers in Indonesia and the roles of these semiotic resources in teaching activities. Through a qualitative case study, two EFL teachers in Bandung and Medan, Indonesia, were purposively selected. Data collection was through a semi-structured interview and document analysis. A six-phase of thematic analysis was employed to analyze the interview results, while a three-step of skimming, reading, and interpretation was used to analyze the documents. This study found that spoken language, pictures, videos, proxemics, gestures, head movements, gaze, and music were the semiotic resources used by both teachers in their teaching. The findings also demonstrated that these semiotic resources were used in the opening, delivering, and closing of the class, explaining learning content, performing interactions with students, checking the students' progress, managing classroom order, showing appreciation, and conducting evaluations. This study implies the crucial roles of all stakeholders in education to help EFL teachers in multimodal knowledge and practical strategy to create better teaching outcomes.